1973
DOI: 10.1161/01.cir.47.3.476
|View full text |Cite
|
Sign up to set email alerts
|

Variant Angina of Prinzmetal with Normal Coronary Arteriograms

Abstract: Variant angina of Prinzmetal has been generally presumed to be caused by a significant focal obstruction in a single major coronary artery which should be an ideal lesion for aortocoronary saphenous vein bypass graft. Recognition of this clinical syndrome would then be of particular diagnostic and therapeutic importance if such a consistent association can be demonstrated. Of five patients with variant angina studied in our cardiac catheterization laboratories, four had normal coronary arteriograms. Two import… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
51
0

Year Published

1975
1975
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 213 publications
(52 citation statements)
references
References 10 publications
(1 reference statement)
1
51
0
Order By: Relevance
“…In about half of VA patients, coronary angiography shows normal coronary arteries (NCAs). 4,5 CSX, on the other hand, is characterized by angina occurring predominantly during effort, ST-segment depression suggesting subendocardial ischemia during exercise stress test and normal coronary arteries during angiography. Coronary microvascular dysfunction (CMVD) is believed to be responsible for angina in most of these patients.…”
Section: Introductionmentioning
confidence: 99%
“…In about half of VA patients, coronary angiography shows normal coronary arteries (NCAs). 4,5 CSX, on the other hand, is characterized by angina occurring predominantly during effort, ST-segment depression suggesting subendocardial ischemia during exercise stress test and normal coronary arteries during angiography. Coronary microvascular dysfunction (CMVD) is believed to be responsible for angina in most of these patients.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, exercise-induced ST-segment elevation has been reported in patients with variant angina. [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] Most have no evidence of left ventricular dysfunction and some have no fixed coronary stenoses. 27 Finally, Bruce et al28 noted ST-segment elevation during exercise testing in 0.5% of asymptomatic, presumably healthy subjects.…”
mentioning
confidence: 99%
“…The development of coronary arteriography provided a clue to confirm that spasm was indeed an important, if not predominant, factor in variant angina. [2][3][4][5][6][7][8] Although aortocoronary bypass surgery has been widely accepted in the treatment of patients with coronary artery disease, its role is controversial in variant angina. A review of the literature9' 10 has shown poor results with coronary artery grafting: persistence of spontaneous pain in spite of patent grafts, high incidence of occlusion of the grafts or postoperative myocardial infarction.…”
Section: In 1959mentioning
confidence: 99%